A statistical analysis of critical quality tools and companies' performance. (10th May 2020) - Cohen, A.; Alhuraish, I.; Robledo, C.; Kobi, A.
Abstract: When implementing continuous improvement methodologies such as Lean and Six Sigma, one crucial aspect is to determine which quality tools to implement to achieve a performance objective. The purpose of this article is to determine the critical quality tools and their effects on companies' performance. The data was collected using a questionnaire that was conducted within French industries, in Pays de la Loire region. A multiple correspondence analysis is performed first to explore and describe the data. Second, ordinal regression models are developed to determine what are the critical quality tools that support the companies' performance in terms of quality, cost, and productivity. This case study shows that the critical quality tools to improve quality performance would be implementing One Piece Flow and GEMBA tools. Next, implementing Value Stream Mapping and Takt Time tools would significantly reduce the cost compared to not implementing those tools. The analysis shows improvement in productivity can be achieved by implementing KANBAN tool. The findings have the potential to guide companies to determine which quality tools are most likely effective in improving quality, productivity, and reducing cost.